Sensor for C4F7N local fault decomposition component detection and preparation method thereof
By using double-layer structure gas sensors in the C4F7N insulation device, combined with SNO2, PD-SNO2 and MOS2-SNO2 gas-sensitive materials and CO3 (HITP) 2 screening layer, the problem of local fault decomposition group in the C4F7N device is solved. High sensitivity and selective testing reduces background gas interference.
Patent Information
- Application Number
- CN202411481712.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In C4F7N insulating devices, local faults lead to the generation of decomposed components, and the prior art is difficult to effectively detect these components, especially under the interference of C4F7N's strong electron affinity and active functional group cyano (-CN).
Using dual-layer structure gas sensors, gas-sensitive materials include SNO2, PD-SNO2, and MOS2-SNO2. It is covered by dripping to the surface of the fork finger electrode and covered with CO3 (HITP) 2 screening materials. Form a double -layer sensor structure.
The high sensitivity and selective testing of the C4F7N fault decomposition group C3F6, CO, and CHF3 have reduced the effects of high -concentration C4F7N background gas interference. The lower limit is 0.195 PPM, 3.12 PPM, and 3.66 PPM, respectively. ability.
Smart Images

Figure CN119375310A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas sensing, and in particular to a sensor for detecting decomposition components of a local fault of C4F7N and a preparation method thereof. Background Art
[0002] SF6 is an insulating gas commonly used in the power industry, with excellent insulation and arc extinguishing performance. But at the same time, SF6 is also a gas with a strong greenhouse effect, and its use is explicitly restricted by the Kyoto Protocol and the Paris Agreement. In order to reduce the dependence of the power system on SF6, experts and scholars in the industry have begun to look for new environmentally friendly gases as insulating media for use in power systems. Among them, C4F7N, as a new type of environmentally friendly gas, has an insulation performance 2.2 times that of SF6, and a greenhouse effect potential value of only 1 / 11 of SF6, which has extremely high application potential. At the operating site, as the operating time of gas-insulated equipment increases, local defects such as free metal particles and poor conductor contact will inevitably appear inside, which will lead to local discharge and local overheating faults. C4F7N will decompose under the action of these faults and generate stable characteristic gas byproducts. By detecting C3F6, CO and CHF3 in these characteristic gas byproducts, it is possible to detect faults inside the equipment in a timely manner and take corresponding operation and maintenance measures. However, due to its strong electron affinity and active functional group cyano (-CN), C4F7N has a strong interference in the detection of its decomposition components. Therefore, in the early stage of the application of C4F7N insulation equipment, it is urgent to propose a gas sensor with simple preparation steps, low cost, working at room temperature and high sensitivity and selectivity to faulty decomposition components to deal with the internal latent faults that may occur during the operation of the equipment. Summary of the invention
[0003] In view of the deficiencies of the above prior art, the present invention provides a sensor for detecting local fault decomposition components of environmentally friendly insulating gas C4F7N and a preparation method thereof. The sensor is used for real-time monitoring of C4F7N fault decomposition components, which can promptly detect faults inside the equipment and facilitate timely implementation of corresponding operation and maintenance measures.
[0004] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0005] A sensor for detecting local fault decomposition components of C4F7N, comprising a gas-sensitive material, a screening layer material and interdigital electrodes, wherein the gas-sensitive material is covered on the surface of the interdigital electrodes, and the screening layer material is covered on the surface of the gas-sensitive material; the screening layer material comprises a two-dimensional metal organic framework material Co3(HITP)2.
[0006] Furthermore, the gas-sensitive material is coated on the surface of the interdigital electrode by drop coating, and the screening layer material is coated on the surface of the gas-sensitive material by screen printing.
[0007] Furthermore, the mass ratio of the gas-sensitive material to the screening layer material is 20:1.
[0008] Furthermore, the preparation steps of the Co3(HITP)2 are as follows:
[0009] S1. Co(NO3)2·6H2O and DMF were mixed, heated to 65°C, and then an aqueous solution of 2,3,6,7,10,11-hexamidotriphenylhexahydrochloride (HATP·6HCl) was added to obtain a mixture;
[0010] S2. Add 2 mol / L NaOAc aqueous solution to the mixture and react at 65 °C for 2 h. Filter the obtained black powder, wash it by centrifugation several times, and dry it to obtain Co3(HITP)2 particles.
[0011] Furthermore, the molar ratio of Co(NO3)2·6H2O to 2,3,6,7,10,11-hexaaminotriphenylhexahydrochloride is 1:0.25.
[0012] Furthermore, the gas-sensitive material includes SnO2 (tin dioxide), Pd-SnO2 (palladium-doped tin dioxide), and MoS2-SnO2 (tin dioxide doped molybdenum disulfide).
[0013] Furthermore, the SnO2 is obtained by electrospinning raw materials including tin dichloride and then calcining them.
[0014] Furthermore, the preparation steps of SnO2 include:
[0015] S1. SnCl2·2H2O, ethanol and N,N-dimethylformamide (DMF) were mixed uniformly at room temperature, and then polyvinyl pyrrolidone (PVP) was added and mixed thoroughly at 60-70 °C to form a viscous colloidal mixture as a precursor solution for electrospinning;
[0016] S2, electrospinning the precursor solution to obtain nanofibers;
[0017] S3. Annealing the nanofibers at 500°C in air for 2 hours to remove PVP and obtain pure SnO2 nanofibers.
[0018] Furthermore, the molecular weight of the polyvinyl pyrrolidone is 1,300,000.
[0019] Furthermore, the mass ratio of SnCl2·2H2O to polyvinyl pyrrolidone is 1:(4.3-4.5).
[0020] Furthermore, the process parameters of the electrospinning are as follows: a constant voltage of 15 kV, an electrode distance of 13 cm, and a pumping rate of 0.8 mL / h.
[0021] Furthermore, the Pd-SnO2 is prepared by a hydrothermal method.
[0022] Furthermore, the preparation steps of Pd-SnO2 include:
[0023] S1. SnCl2·2H2O, C6H5Na3O7·2H2O, PdCl2, ethanol and water are fully mixed at room temperature to obtain a precursor suspension;
[0024] S2. The precursor suspension is reacted at 180°C for 12 h, cooled to room temperature, filtered, centrifuged, washed, and dried to obtain Pd-SnO2 particles.
[0025] Furthermore, the molar ratio of SnCl2·2H2O, C6H5Na3O7·2H2O, and PdCl2 is 5:10:0.2.
[0026] Furthermore, the MoS2-SnO2 is obtained by growing granular SnO2 on the surface of MoS2 nanoflowers.
[0027] Furthermore, the preparation steps of MoS2-SnO2 include:
[0028] S1. Na2MoO4·2H2O, CH3CSNH2 and water are mixed uniformly at room temperature, and then cetyltrimethylammonium bromide (CTAB) is added and mixed uniformly to obtain a mixture;
[0029] S2, reacting the mixture at 180 °C for 24 h, cooling to room temperature, centrifuging, washing, and drying to obtain MoS2 nanoflowers;
[0030] S3. After MoS2 nanoflowers, SnCl2·2H2O and water are fully mixed, reacted at 180 °C for 12 h, cooled to room temperature, and then repeatedly centrifuged, washed and dried to obtain MoS2-SnO2 particles.
[0031] Furthermore, the mass ratio of Na2MoO4·2H2O, CH3CSNH2 and hexadecyltrimethylammonium bromide is 1:1:0.3.
[0032] Furthermore, the mass ratio of the MoS2 nanoflowers to SnCl2·2H2O is 4:1.
[0033] The method for preparing the sensor for detecting the decomposition components of C4F7N local fault comprises the following steps:
[0034] (1) Prepare SnO2, Pd-SnO2, and MoS2-SnO2 solutions respectively, drop the solutions onto the surface of the interdigital electrode, and form a gas-sensitive layer after vacuum drying at 65 °C;
[0035] (2) The screening layer material solution is covered on the surface of the gas-sensitive layer by screen printing, and after vacuum drying at 65 °C, a screening layer is formed to obtain a sensor for detecting the decomposition components of C4F7N local faults.
[0036] Furthermore, the concentrations of the SnO2, Pd-SnO2, and MoS2-SnO2 solutions are all 1 mg / 40 μL.
[0037] Furthermore, the concentration of the screening layer material solution is 1 mg / 200 μL.
[0038] The design principle of the present invention is as follows: SnO2, Pd-SnO2 and MoS2-SnO2 are used as gas-sensitive materials in the present invention, and the gas-sensitive materials are coated on the surface of the interdigital electrodes by drop coating, and then the screening layer material Co3(HITP)2 is coated on the surface of the gas-sensitive material by screen printing, thereby forming a double-layer sensing structure. When the Co3(HITP)2 screening layer in the present invention comes into contact with C4F7N gas molecules, the Co in Co3(HITP)2 2+ The ions will interact strongly with the -CN groups in the C4F7N molecules, so that the C4F7N molecules in the background gas are bound to the surface of the Co3(HITP)2 screening layer; the micropores in Co3(HITP)2 can provide diffusion channels for the fault decomposition component gas molecules, so that the gas-sensitive layer under the screening layer can contact the target gas molecules and transfer charges, resulting in a selective response; SnO2, Pd-SnO2 and MoS2-SnO2 in the gas-sensitive layer can selectively respond to the components C3F6, CO and CHF3 produced by the decomposition of C4F7N based on the active sites in the structure, thereby forming a sensor array and realizing qualitative and quantitative identification of the mixed gas after processing by the KPCA algorithm.
[0039] Compared with the prior art, the present invention is beneficial in that:
[0040] (1) The double-layer structure gas sensor based on Co3(HITP)2 screening and filtration provided by the present invention is used for real-time monitoring of C4F7N fault decomposition components, which can promptly detect faults inside the equipment and take corresponding operation and maintenance measures in a timely manner; and the sensor has a low detection limit, and its detection lower limits for C3F6, CO, and CHF3 are 0.195 ppm, 3.12 ppm, and 3.66 ppm, respectively.
[0041] (2) The present invention forms a double-layer structure sensor by coating a Co3(HITP)2 screening layer on the surface of different gas-sensitive materials. On the basis of retaining the selectivity of the original gas-sensitive material, the sensor's ability to suppress interference from high-concentration C4F7N background gas is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The morphology of the SnO2 nanofiber provided by the present invention under a scanning electron microscope;
[0043] Figure 2 The morphology of the Pd-SnO2 particles provided by the present invention under a scanning electron microscope;
[0044] Figure 3 The morphology of the MoS2-SnO2 particles provided by the present invention under a scanning electron microscope;
[0045] Figure 4 The morphology of the Co3(HITP)2 particles provided by the present invention under a scanning electron microscope;
[0046] Figure 5 This is a comparison chart of the C4F7N responses of the sensor pair prepared in Example 1 and Comparative Example 1.
[0047] Figure 6 This is a diagram showing the effect of the sensor data of a single gas and a mixed gas prepared in Example 1 after KPCA processing. DETAILED DESCRIPTION
[0048] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The present invention provides a sensor for detecting local fault decomposition components of C4F7N, comprising a gas-sensitive material, a screening layer material and interdigital electrodes, wherein the gas-sensitive material is covered on the surface of the interdigital electrodes, and the screening layer material is covered on the surface of the gas-sensitive material; the screening layer material comprises a two-dimensional metal-organic framework material Co3(HITP)2.
[0050] In the following specific embodiments, the gas-sensitive material is coated on the surface of the interdigital electrode by drop coating, and the screening layer material is coated on the surface of the gas-sensitive material by screen printing.
[0051] In the following specific embodiments, the mass ratio of the gas-sensitive material to the screening layer material is 20:1.
[0052] In the following specific embodiments, the gas-sensitive material includes SnO2 (tin dioxide), Pd-SnO2 (palladium-doped tin dioxide), and MoS2-SnO2 (tin dioxide doped molybdenum disulfide).
[0053] In the following specific examples, the SnO2 is obtained by electrospinning and then calcining raw materials including tin dichloride; the Pd-SnO2 particles are prepared by a hydrothermal method; the MoS2-SnO2 is obtained by growing granular SnO2 on the surface of MoS2 nanoflowers;
[0054] Wherein, the preparation steps of SnO2 are specifically as follows:
[0055] S1. Add 0.328 g of SnCl2·2H2O, 5 mL of ethanol and 5 mL of DMF into a reagent bottle and stir at room temperature for 10 min. Then add 1.445 g of polyvinyl pyrrolidone (PVP, molecular weight = 1,300,000) and stir at 65°C for 8 h to form a viscous colloidal mixture as a precursor solution for electrospinning.
[0056] S2, the precursor solution was loaded into a plastic syringe, and electrospun at a constant voltage of 15 kV, an electrode distance of 13 cm, and a pumping rate of 0.8 mL / h to obtain nanofibers;
[0057] S3, annealing the nanofibers in a muffle furnace at 500 ° C in air for 2 hours to remove PVP, and finally obtaining pure SnO2 nanofibers. The morphology of the SnO2 nanofibers under a scanning electron microscope is shown in FIG. Figure 1 shown.
[0058] The preparation steps of the Pd-SnO2 are as follows:
[0059] S1. Add 1.128 g SnCl2·2H2O, 2.941 g C6H5Na3O7·2H2O, 0.0369 g PdCl2, 20 mL ethanol and 20 mL deionized water into a beaker and stir well at room temperature for 1 h to obtain a precursor suspension.
[0060] S2. The precursor suspension was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C for 12 h. After the reaction product was cooled to room temperature, it was filtered out of the solution, then centrifuged and washed several times with ethanol and deionized water, and finally freeze-dried to obtain Pd-SnO2 particles. The morphology of the Pd-SnO2 particles under a scanning electron microscope is shown in FIG. Figure 2 shown.
[0061] The preparation steps of the MoS2-SnO2 are specifically as follows:
[0062] S1. Add 1 g of Na2MoO4·2H2O, 1 g of CH3CSNH2 and 50 mL of deionized water into a beaker, stir at room temperature for 10 min, then add 0.3 g of hexadecyltrimethylammonium bromide (CTAB) into the above solution, and continue stirring for 30 min to obtain a mixture;
[0063] S2, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180 °C for 24 h; the precipitate was separated by centrifugation, and purified by washing with ethanol and deionized water for multiple times, and MoS2 nanoflowers were obtained after freeze-drying for 12 hours;
[0064] S3, MoS2 nanoflowers and SnCl2·2H2O were mixed in deionized water at a mass ratio of 4:1, and the mixture was fully stirred for 1 h to obtain a mixture, and the mixture was subjected to a hydrothermal reaction at 180 °C for 12 h. After cooling to room temperature, the product was purified by repeated centrifugation and washing with ethanol and deionized water, and MoS2-SnO2 particles were obtained by freeze drying. The morphology of the MoS2-SnO2 particles under a scanning electron microscope is shown in FIG. Figure 3 shown.
[0065] In the following specific examples, the preparation steps of Co3(HITP)2 are as follows:
[0066] S1. Add 27.1 mg of Co(NO3)2·6H2O and 1.5 mL of N,N-dimethylformamide (DMF) into a beaker and heat to 65°C. Then, dissolve 8 mg of 2,3,6,7,10,11-hexamidotriphenylhexahydrochloride (HATP·6HCl) in 1.5 mL of deionized water and add the HATP·6HCl dropwise to the solution to obtain a mixture.
[0067] S2. Add 2 mL of 2 mol / L NaOAc aqueous solution to the mixture, stir continuously at 65 °C for 2 h, filter the obtained black powder, and then centrifuge and wash it with deionized water and ethanol for multiple times, and freeze-dry to obtain Co3(HITP)2 particles. The morphology of the Co3(HITP)2 particles under a scanning electron microscope is shown in FIG. Figure 4 shown.
[0068] Example 1
[0069] A sensor for detecting decomposition components of C4F7N local fault, the preparation method comprising the following steps:
[0070] S1. Prepare SnO2, Pd-SnO2 and MoS2-SnO2 into 1 mg / 40 μL solutions respectively. After 1 h of ultrasound, add 10 μL of each solution onto the surface of the interdigital electrode. After vacuum drying at 65 °C for 6 h, a gas-sensitive layer is formed.
[0071] S2. Prepare Co3(HITP)2 into a 1 mg / 200 μL solution. After ultrasonic treatment for 1 h, add 2.5 μL of the solution to the surface of the dry gas-sensitive layer by screen printing. Then, dry it in a vacuum oven at 65 °C for 6 h to obtain a sensor for detecting the decomposition components of local faults in C4F7N.
[0072] Comparative Example 1
[0073] A sensor for detecting decomposition components of C4F7N local fault, the preparation method comprising the following steps:
[0074] S1. Prepare SnO2, Pd-SnO2 and MoS2-SnO2 into 1 mg / 40 μL solutions respectively. After 1 h of ultrasound, add 10 μL of each solution to the surface of the interdigital electrode. After vacuum drying at 65 °C for 6 h, a sensor for detecting the decomposition components of local faults in C4F7N is obtained.
[0075] At room temperature, the sensors prepared in Example 1 and Comparative Example 1 were placed in resistance detection equipment, and 6% C4F7N / 94% CO2 mixed gas was introduced into the equipment for a period of time until the resistance of the sensor was stable. Thereafter, different types and concentrations of fault decomposition component gases (C3F6, CO, CHF3) were introduced into the equipment, and the change in the resistance of the sensor was observed. When the response was close to saturation, 6% C4F7N / 94% CO2 mixed gas was introduced again. The test results are shown in Figure 2. Figure 5 As shown. Figure 5 It can be seen that the presence of the Co3(HITP)2 screening layer greatly improves the sensitivity of the sensor to C3F6, CO, and CHF3. In addition, the response data of the sensor prepared in Example 1 to single gas and mixed gas are processed by KPCA. Figure 6 Given in. Figure 6 It can be seen that the dotted areas composed of different types of gases do not overlap, indicating that the sensor has a certain qualitative and quantitative recognition ability for single gases and mixed gases.
[0076] In summary, the present invention uses SnO2, Pd-SnO2 and MoS2-SnO2 as gas-sensitive materials, and the gas-sensitive materials are coated on the surface of the interdigital electrode by drip coating, and then the screening layer material Co3(HITP)2 is coated on the surface of the gas-sensitive material by screen printing, thereby forming a double-layer sensing structure. The double-layer structure sensor array can detect its decomposition components C3F6, CO, and CHF3 under the strong interference of C4F7N background gas. The three gas-sensitive materials have certain response selectivity to the three gases, and the detection limits are 0.195 ppm, 3.12 ppm, and 3.66 ppm respectively; and the experimental data can form non-overlapping sample points under the KPCA algorithm, indicating that the double-layer structure sensor array has certain qualitative and quantitative recognition capabilities for mixed gases.
[0077] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A sensor for detecting decomposition components of C4F7N local fault, characterized in that: It comprises a gas-sensitive material, a screening layer material and an interdigital electrode, wherein the gas-sensitive material covers the surface of the interdigital electrode, and the screening layer material covers the surface of the gas-sensitive material; the screening layer material comprises Co3(HITP)2.
2. A sensor for detecting decomposition components of C4F7N local fault according to claim 1, characterized in that: The mass ratio of the gas-sensitive material to the screening layer material is 20:
1.
3. A sensor for detecting decomposition components of C4F7N local fault according to claim 1, characterized in that: The preparation steps of Co3(HITP)2 are as follows: S1. Mix Co(NO3)2·6H2O and DMF, heat to 65°C, and then add 2,3,6,7,10,11-hexaaminotriphenylhexahydrochloride solution to obtain a mixture; S2. Add NaOAc solution to the mixture, react at 65 °C for 2 h, filter, centrifuge and wash multiple times, and dry to obtain Co3(HITP)2 particles.
4. A sensor for detecting decomposition components of C4F7N local fault according to claim 3, characterized in that: The molar ratio of the Co(NO3)2·6H2O to 2,3,6,7,10,11-hexaaminotriphenylhexahydrochloride is 1:0.
25.
5. A sensor for detecting decomposition components of C4F7N local fault according to claim 1, characterized in that: The gas-sensitive materials include SnO2, Pd-SnO2, and MoS2-SnO2.
6. A sensor for detecting decomposition components of C4F7N local fault according to claim 5, characterized in that: The preparation steps of SnO2 include: S1. Mix SnCl2·2H2O, ethanol and DMF evenly, then add polyvinyl pyrrolidone and mix thoroughly at 60-70 °C to form a viscous colloidal mixture as a precursor solution for electrospinning; S2, electrospinning the precursor solution to obtain nanofibers; S3. Annealing the nanofibers at 500°C to obtain pure SnO2 nanofibers.
7. A sensor for detecting decomposition components of C4F7N local fault according to claim 5, characterized in that: The preparation steps of the Pd-SnO2 include: S1. SnCl2·2H2O, C6H5Na3O7·2H2O, PdCl2, ethanol and water are fully mixed to obtain a precursor suspension; S2. The precursor suspension is reacted at 180°C for 12 h, cooled to room temperature, filtered, centrifuged, washed, and dried to obtain Pd-SnO2 particles.
8. A sensor for detecting decomposition components of C4F7N local fault according to claim 7, characterized in that: The molar ratio of SnCl2·2H2O, C6H5Na3O7·2H2O and PdCl2 is 5:10:0.
2.
9. A sensor for detecting decomposition components of C4F7N local fault according to claim 5, characterized in that: The preparation steps of MoS2-SnO2 include: S1. Na2MoO4·2H2O, CH3CSNH2 and water are mixed evenly, and then cetyltrimethylammonium bromide is added and mixed evenly to obtain a mixture; S2, reacting the mixture at 180 °C for 24 h, cooling to room temperature, centrifuging, washing, and drying to obtain MoS2 nanoflowers; S3. After MoS2 nanoflowers, SnCl2·2H2O and water are fully mixed, reacted at 180 °C for 12 h, cooled to room temperature, and then repeatedly centrifuged, washed and dried to obtain MoS2-SnO2 particles.
10. A method for preparing a sensor for detecting decomposition components of C4F7N local fault according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Prepare SnO2, Pd-SnO2, and MoS2-SnO2 solutions respectively, drop the solutions onto the surface of the interdigital electrode, and form a gas-sensitive layer after vacuum drying; (2) The Co3(HITP)2 solution was coated onto the surface of the gas-sensitive layer by screen printing and then vacuum dried to obtain a sensor for detecting the decomposition components of C4F7N local fault.
Citation Information
Patent Citations
Gas-sensitive material for detecting NO2 and method for manufacturing gas-sensitive element made of gas-sensitive material
CN105606660A
Ring main unit C4F7N mixed gas detection method and device
CN114527081A
Conductive MOF (Metal Organic Framework) modified gas sensitive material as well as preparation method and application thereof
CN114778614A
Sensing device for leakage of environment-friendly insulating gas perfluoroisobutyronitrile, detection method and application
CN115586222A
NH3 gas sensor based on high-conductivity bimetallic Co / Cu-HHTP sensitive material and preparation method thereof
CN116482189A
Cited By
Resistance type gas sensor based on PAN and UiO-66 compounding and preparation and application thereof
CN121476316A
Application of PES / UiO-66 composite membrane as gas sensitive material to detection of characteristic decomposition component CO of C4F7N / CO2 mixed gas
CN121612941A
Application of PES / UiO-66 composite membrane in detection of characteristic decomposition component CO of C4F7N / CO2 mixed gas as gas sensitive material
CN121612941B
Gas sensitive material based on PVDF / ZIF-8 composite nanofiber membrane as well as preparation method and application of gas sensitive material
CN121653957A
A gas-sensitive material based on a PVDF / ZIF-8 composite nanofiber membrane, a preparation method and application thereof
CN121653957B